Exogenous γ-aminobutyric acid (GABA) mitigated salinity-induced impairments in mungbean plants by regulating their nitrogen metabolism and antioxidant potential - Ullah, Abd; Ali, Iftikhar; Noor, Javaria; Zeng, Fanjiang; Bawazeer, Sami; Eldin, Sayed M; Asghar, Muhammad Ahsan; Javed, Hafiz Hassan; Saleem, Khansa; Ullah, Sami; Ali, Haider (Frontiers in Plant Science, 2023)
Background Increasing soil salinization has a detrimental effect on agricultural productivity.Therefore, strategies are needed to induce salinity-tolerance in crop species for sustainable foodproduction. γ-aminobutyric acid (GABA) plays a key role in regulating plant salinity stresstolerance. However, it remains largely unknown how mungbean plants (Vigna radiata L.) respondto exogenous GABA under salinity stress. Methods Thus, we evaluated the effect of exogenous GABA (1.5 mM) on the growth and physiobiochemicalresponse mechanism of mungbean plants to saline stress (0-, 50-, and 100 mM [NaCland Na2SO4, at a 1:1 molar ratio]). Results Increased saline stress adversely affected mungbean plants' growth and metabolism. Forinstance, leaf-stem-root biomass (34- and 56%, 31- and 53%, and 27- and 56% under 50- and 100mM, respectively]) and chlorophyll concentrations declined. The carotenoid level increased (10%)at 50 mM and remained unaffected at 100 mM. Hydrogen peroxide (H2O2), malondialdehyde(MDA), osmolytes (soluble sugars, soluble proteins, proline), total phenolic content, andenzymatic activities of superoxide dismutase (SOD), ascorbate peroxidase (APX), peroxidase(POD), glutathione reductase (GTR), and polyphenol oxidation (PPO) were significantlyincreased. In leaves, salinity caused a significant increase in Na+ concentration but a decrease inK+ concentration, resulting in a low K+/Na+ concentration (51- and 71% under 50- and 100- mMstress). Additionally, nitrogen concentration and the activities of nitrate reductase (NR) andglutamine synthetase (GS) decreased significantly. The reduction in glutamate synthase (GOGAT)activity was only significant (65%) at 100 mM stress. Exogenous GABA decreased Na+, H2O2,and MDA concentrations but enhanced photosynthetic pigments, K+ and K+/Na+ ratio, Nmetabolism, osmolytes, and enzymatic antioxidant activities, thus reducing salinity-associatedstress damages, resulting in improved growth and biomass. Conclusion Exogenous GABA may have improved the salinity tolerance of mungbean plants by maintaining their morpho-physiological responses and reducing the accumulation of harmfulsubstances under salinity. Future molecular studies can contribute to a better understanding of themolecular mechanisms by which GABA regulates mungbean salinity tolerance.